2023
DOI: 10.3389/fcimb.2023.1178736
|View full text |Cite
|
Sign up to set email alerts
|

Genome organization and genomics in Chlamydia: whole genome sequencing increases understanding of chlamydial virulence, evolution, and phylogeny

Abstract: The genus Chlamydia contains important obligate intracellular bacterial pathogens to humans and animals, including C. trachomatis and C. pneumoniae. Since 1998, when the first Chlamydia genome was published, our understanding of how these microbes interact, evolved and adapted to different intracellular host environments has been transformed due to the expansion of chlamydial genomes. This review explores the current state of knowledge in Chlamydia genomics and how whole genome sequencing has revolutionised ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 162 publications
(336 reference statements)
0
7
1
Order By: Relevance
“…Previously, a study by Moran et al [62] demonstrated that obligate association with host tissues promotes genome reduction in bacteria. Studies on Ct suggested that genome streamlining results from its co-evolution within the eukaryotic host [48,[63][64][65][66], and is facilitated by its ability to acquire essential metabolites from its host [62,[67][68][69]. Our observations contradict prior speculations by Bohlin.…”
Section: Discussioncontrasting
confidence: 79%
“…Previously, a study by Moran et al [62] demonstrated that obligate association with host tissues promotes genome reduction in bacteria. Studies on Ct suggested that genome streamlining results from its co-evolution within the eukaryotic host [48,[63][64][65][66], and is facilitated by its ability to acquire essential metabolites from its host [62,[67][68][69]. Our observations contradict prior speculations by Bohlin.…”
Section: Discussioncontrasting
confidence: 79%
“…psittaci Agilent probes and WGS costs in this study were estimated at AUD$17 000 for 16 samples). Comparatively MLST (combined with omp A genotyping) is a cost-effective and less technical tool for chlamydial molecular epidemiology studies [4, 6, 10]. This study additionally obtained 26 C .…”
Section: Discussionmentioning
confidence: 99%
“…This genomic data limitation is particularly evident for avian strains from Australia ( n =8) and New Zealand (known as Aotearoa in the Māori language) ( n =0). Without WGS, many global studies commonly utilise omp A genotyping and/or multilocus sequence typing (MLST) to provide the initial identity of infecting strains [4]. Recent studies in Australia have also detected C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact function of these genes within these avian C. abortus strains is still to be elucidated, there is increasing evidence that the chlamydial plasmid plays a vital role in the virulence, persistent infection and pathogenicity in other infecting strains [29]. Therefore, the presence of a chlamydial plasmid within these avian C.…”
Section: Discussionmentioning
confidence: 99%